Grassfields Stories from Cameroon. - Vakunta, Peter Wuteh (Langaa RPCIG, 2008)
Grassfields Stories from Cameroon is an anthology of short stories. It comprises animal trickster tales, bird survival tales, and human-interest stories. The compendium is a reflection of the mores, cultures, and value systems of the indigenous peoples of the Northwest Province of Cameroon. It is motivated by the author's keen interest in the preservation of Cameroonian oral traditions in written form. These stories deal with the day-to-day life of the sedentary and the globe-trotter. Each story is sufficient onto itself. The author has intentionally avoided chronology in the order of presenta.